Influence of Psychoticism on Crime Scene Behavior of Murderers - Kolarević, Dag (Zbornik Instituta za kriminološka i sociološka istraživanja, 2007)
In this work, the first instrumental-expressive typology was confirmed on a sample of 152 convicted murderers from Serbian prisons. Then, instrumental and expressive murderers were compared in relation to the dimension of psychoticism. The theoretical framework for this research was Eysenck’s assumptions about the influence of personality traits upon criminal behaviour. Redefined concept of psychoticism as an indicator of personality integration with biological determination has emerged as an important factor in the crime scene behaviour of murderers.